Бродильно-формуючий агрегат (Панент на винахід № 85296) - Теличкун, Володимир Іванович; Чепелюк, Олена Олександрівна; Шкляр, Світлана Вікторівна; Теличкун, Юлія Станіславівна; Губеня, Олексій Олександрович (My University, 2009)
З метою скорочення машинно-апаратурної схеми, зменшення витрат на утримання і експлуатацію обладнання, розроблено бродильно-формуючий агрегат, що містить робочу камеру, в середині якої розташований нагнітальний гумовий рукав, а знизу камери розташована формуюча матриця. Агрегат відрізняється тим, що робоча камера використана як ємність для бродіння тістового напівфабрикату під тиском до етапу його формування, а гумовий рукав – як робочий орган, що діє на тісто. To reduce machine-equipment schemes, reduction of costs for maintenance and operation of equipment fermentation-molding unit are developed. It consists of a processing chamber inside of which the rubber sleeve pressing is and bottom of the camera a matrix form is. The unit is characterized in that the processing chamber is used as fermentation tank for semifinished product under pressure and the rubber sleeve - like operating element acting on the dough. It containing the working chamber, inside of which is forcing the rubber sleeve and bottom of the camera the matrix is molding. Unit is the fact that the working chamber is used as a vessel for the semifinished product fermentation under pressure before the stage of its formation, and the rubber sleeve is used as a working body, acting on the dough.
Keywords: бродильно-формувальний агрегат; тістовий напівфабрикат; тиск; fermentation-molding unit; semifinished product; pressure; кафедра машин і апаратів харчових та фармацевтичних виробництв